Sodium Thiosulfate Penta-hydrate as thermal energy storage for increase solar distillation productivity in Indonesia - Ni Ketut, Caturwati; Yusuf, Yusvardi (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The maximum temperature of water in solar distillate system determines the effectiveness of applying a Phase Change Materials (PCMs) as Thermal Energy Storage (TES). This paper evaluates the effectiveness of using Sodium Thiosulfate Penta-Hydrate as PCMs for double slope solar distillation systems operating in the Cilegon-Indonesia. The results of 5 tests during the day showed the average water temperature value in the basin with PCMs reaching 42.4 ?C and without PCMs reaching 42.6 ?C. While the maximum average temperature of water in the basin reaches 49.56 C for systems without PCMs and 49.2 C for systems with PCMs. Addition of PCMs in water increases distillate production at night if the maximum temperature of the water exceeds the melting point of the PCMs material (48 C). This is occurs when the maximum water temperature in the basin reaches 51 C, distillate production in systems with PCMs is 38% more than systems without PCMs.